The Effectiveness of Physics Learning for Biology Students Based on Interactive Posters Using SWOT Analysis - Baiq Revalina Restu Khaunifar; Indah Nur Gusfiana; Anisa, Anisa; Najma Aldina Roshin; Deatun Zahra; Elen Renata Putra; Kormil Saputra (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This study aims to analyze the effectiveness of interactive poster-based physics learning for biology students through a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach. Learning is designed to integrate physics concepts that are relevant to biology, such as fluid mechanics, optics, and thermodynamics, with attractive visualizations using interactive posters. The research method uses a quantitative-descriptive approach involving 60 biology students as research subjects. Data were collected through distributed questionnaires, then analyzed using the SWOT framework to identify the advantages, disadvantages, opportunities, and challenges of interactive poster-based learning. The results showed that using this interactive poster was able to improve students' understanding of physics concepts by 61.1% compared to conventional learning, mainly because the visualization helped improve information retention (making them remember the material better). The SWOT analysis showed that the main advantage of this learning is the relevance of the material to the needs of biology students, as well as its ability to simplify complex concepts. However, the main weakness is the limited time available for in-depth discussions. Great opportunities lie in the potential for developing more interactive digital posters, while the main challenge is the lack of supporting facilities.  Overall, interactive poster-based learning is effective as an innovative alternative in supporting the understanding of physics concepts for biology students.